Pengaruh Web Trace and Tracking, Ketepatan Waktu Pengiriman, dan Persepsi Harga Terhadap Kepuasan Konsumen di JNE Sales Counter Tempurejo Kediri - Tama, Gensa Fredy; Prasasti, Karari Budi; Munawaroh, Nuril Aulia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Increasingly fierce competition in the shipping industry in the digital age demands continuous service innovation, necessitating an in-depth analysis of various factors that influence customer satisfaction levels. This study aims to analyze the influence of Web Trace and Tracking, Delivery Timeliness, and Price Perception on Customer Satisfaction at PT. JNE Sales Counter Tempurejo. The method used is descriptive quantitative with a sample of 140 respondents. Data was collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The results of the study indicate that the three independent variables have a positive and significant influence on customer satisfaction, both partially and simultaneously, with a coefficient of determination of 55%. These findings confirm that optimizing digital features such as Web Trace and Tracking, improving delivery timeliness, and implementing competitive pricing strategies can enhance consumer satisfaction and loyalty. This study provides strategic implications for the development of digital-based logistics services and suggests further research considering other variables such as brand image and customer loyalty.